2016
DOI: 10.1136/ejhpharm-2016-000903
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of caffeine, carvedilol, clomipramine hydrochloride, folic acid, hydrochlorothiazide, loperamide hydrochloride, methotrexate, nadolol, naltrexone hydrochloride and pentoxifylline in SyrSpend SF PH4 oral suspensions

Abstract: ObjectivesThe objective of this study was to evaluate the compatibility of 10 commonly used active pharmaceutical ingredients (APIs) compounded in oral suspensions using a globally available suspending vehicle (SyrSpend SF PH4 liquid): caffeine 10.0 mg/mL, carvedilol 1.0 mg/mL, clomipramine hydrochloride 5.0 mg/mL, folic acid 1.0 mg/mL, hydrochlorothiazide 5.0 mg/mL, loperamide hydrochloride 1.0 mg/mL, methotrexate 2.5 mg/mL, nadolol 10.0 mg/mL, naltrexone hydrochloride 1.0 mg/mL and pentoxifylline 20.0 mg/mL,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…Regardless of the type of storage conditions, the proportion of the initial concentration of dexamethasone, hydrochlorothiazide, phenytoin, or spironolactone remaining was within the limit set by the U.S. Pharmacopeia [26], meaning that the oral suspensions of each drug compounded using Syrspend® SF PH4 Dry were stable up to 60 days both at room temperature or under refrigeration. This result is similar to or greater than the stability period reported by others [9,10,11,12,13,14,15]. The physicochemical stability of the four oral liquid dosage forms was investigated for a period of 60 days since the microbiological stability of suspensions compounded using Syrspend® SF PH4 Dry has been demonstrated by the manufacturer over the same period [30].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Regardless of the type of storage conditions, the proportion of the initial concentration of dexamethasone, hydrochlorothiazide, phenytoin, or spironolactone remaining was within the limit set by the U.S. Pharmacopeia [26], meaning that the oral suspensions of each drug compounded using Syrspend® SF PH4 Dry were stable up to 60 days both at room temperature or under refrigeration. This result is similar to or greater than the stability period reported by others [9,10,11,12,13,14,15]. The physicochemical stability of the four oral liquid dosage forms was investigated for a period of 60 days since the microbiological stability of suspensions compounded using Syrspend® SF PH4 Dry has been demonstrated by the manufacturer over the same period [30].…”
Section: Discussionsupporting
confidence: 78%
“…To enable the appropriate volume of administration (preferably ≤1 mL for a newborn), according to the dose required in their therapeutic uses [6,8,28], we chose to prepare oral liquid dosage forms at a target concentration of 5 mg/mL for spironolactone, dexamethasone, and phenytoin and 2 mg/mL for hydrochlorothiazide. According to the literature, other authors have reported similar concentrations for oral liquid compounded preparations of the same APIs [10,13,15]. Some authors have proposed oral liquid dosage forms with lower strengths due to different therapeutic uses [12,14] or higher strengths since they were used in older children [9,11].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“… Carvedilol [12] is a racemic mixture where the S(-) enantiomer is a beta adrenoceptor blocker and the R(+) enantiomer is both a beta and alpha-1 adrenoceptor blocker. It is currently used to treat heart failure, left ventricular dysfunction, and hypertension.…”
Section: Low Solubility / High Permeability (Bcs Class Ii)mentioning
confidence: 99%
“…Compatibility results with SyrSpend SF have been published for more than 70 different APIs. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] In all of these studies, the compatibility was assessed by measuring the percentage recovery at varying time points throughout a 90-day period at controlled room and/or at controlled refrigerated temperature. The majority of the compatibility studies have been performed with raw pharmaceutical APIs.…”
mentioning
confidence: 99%